2011
DOI: 10.1007/s00213-011-2347-8
|View full text |Cite
|
Sign up to set email alerts
|

Dronabinol, a cannabinoid agonist, reduces hair pulling in trichotillomania: a pilot study

Abstract: This study, the first to examine a cannabinoid agonist in the treatment of trichotillomania, found that dronabinol demonstrated statistically significant reductions in trichotillomania symptoms, in the absence of negative cognitive effects. Pharmacological modulation of the cannabinoid system may prove useful in controlling a range of compulsive behaviors. Given the small sample and open-label design, however larger placebo-controlled studies incorporating cognitive measures are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
2
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 57 publications
1
44
2
3
Order By: Relevance
“…Several studies have found that synthetic cannabinoids can reduce anxiety (Fabre and McLendon, 1981;Grant et al, 2011;Schindler et al, 2008). Cannabinoid effects on anxietylike behavior in rodents have recently been described (Braida et al, 2007;Jiang et al, 2005;Patel and Hillard, 2006).…”
Section: Anxietymentioning
confidence: 99%
“…Several studies have found that synthetic cannabinoids can reduce anxiety (Fabre and McLendon, 1981;Grant et al, 2011;Schindler et al, 2008). Cannabinoid effects on anxietylike behavior in rodents have recently been described (Braida et al, 2007;Jiang et al, 2005;Patel and Hillard, 2006).…”
Section: Anxietymentioning
confidence: 99%
“…The latter interpretation is supported by the observation that anxiety-spectrum disturbances and traumas in early developmental stages are a strong predictor for later cannabis use disorders [124-127]; furthermore, several lines of evidence suggest that the anxiolytic effects of THC may partially account for the high prevalence of cannabis use in patients affected by PTSD [128-131] and OCD [132]. Accordingly, recent clinical studies have shown that THC elicits therapeutic effects in OCD [133] and trichotillomania, an impulse-control disorder characterized by compulsive hair-pulling [134]. Nevertheless, prospective analyses show that cannabis use and dependence increase the risk for development of panic disorder [135], suggesting that the effect of cannabis may vary with respect to the nosological entities within the spectrum of anxiety disorders.…”
Section: Effects Of Cannabis and Cannabinoid Agents On Anxietymentioning
confidence: 99%
“…This was a 12-week open-label treatment study involving 14 female participants with TTM [22]. MGH-HPS scores decreased from a mean of 16.5 ± 4.4 at baseline to 8.7 ± 5.5 at study endpoint (p = 0.001).…”
Section: Cannabinoid Agonistsmentioning
confidence: 99%